Physical Responses of Pinctada fucata to Salinity Stress - Yang, Jingru; Yang, Jinling; Chen, Mingqiang; Fu, Zhengyi; Sun, Jing; Yu, Gang; Wang, Aimin; Ma, Zhenhua; Gu, Zhifeng (Frontiers in Marine Science, 2022)
This study was conducted to understand the changes of physiological and biochemical indexes of black and red shell Pinctada fucata under acute high and low salt stress. In this study, the salinity of 35‰ was used as the control, while the salinities of 20 and 50% salinity were used as the low and high salt treatment groups, respectively. The osmotic pressure (OSM) and ion concentration in the hemolymph, Na+-K+ -ATPase (NKA) activity and respiratory metabolism in gills, and antioxidant and immune (non) enzymes in the hepatopancreas of P. fucata with two shell colors were compared and analyzed at the time periods of 1.5 and 3 h post-salinity stress. The results showed that the OSM and inorganic ion (Na+, Ca2+, and Cl–) concentration in the hemolymph of the black and red P. fucata increased significantly with the increase of salinity after the time periods of 1.5 and 3 h. At 3 h, the black P. fucata NKA activity decreased significantly with the increase of salinity, while red P. fucata reached the highest value at high salinity. The succinate dehydrogenase (SDH) and lactate dehydrogenase (LDH) activities of red P. fucata showed U-shaped and inverted U-shaped distributions with the increase of salinity after 1.5 h, respectively. With the increase of salinity, the phenoloxidase (POX) activity of red and black P. fucata showed inverted U-shaped and U-shaped distributions, respectively. The contents of glutathione (GSH) and vitamin C (VC) in black P. fucata decreased significantly with the increase of salinity at 1.5 and 3 h. Red P. fucata GSH and VC reached their maximum value in the 1.5-h low salinity group and 3-h high salinity group. The vitamin E (VE) content in black P. fucata increased significantly with the increase of salinity at 1.5 h, and reached the maximum at 3 h in the control group. Red P. fucata VE reached the maximum at 1.5 and 3 h in the control group. The results obtained from the present study revealed that the sensitivity of P. fucata to salinity varied in shell color. Compared to black P. fucata, red P. fucata responds more quickly to sharp salinity changes, thereby reducing more likely damage. Compared with a high salt environment, P. fucata was more adaptable to the changes of acute low salt environment. The results obtained from the present study provide the physical references for subsequent selective breeding of this species.